PTTG1 promotes M2 macrophage polarization via the cGMP-PKG signaling pathway and facilitates EMT progression in human epithelial ovarian cancer cells - Liang Tian; Liyun Liu; Chunlou Wang; Yan Kong; Zhigang Miao; Qing Yao; He Zhang; Yuehong Li (Discover Oncology)
Abstract Epithelial Ovarian Cancer (EOC) is complex and heterogeneous, making accurate prognosis and treatment prediction difficult. New therapeutic targets and their mechanisms are urgently needed. This study explored the role of PTTG1 in ovarian cancer via the cGMP-PKG signaling pathway, focusing on its effects on M2 macrophage polarization and EMT progression in EOC cells. Using the GSE135886 database, we performed differential gene expression, pathway enrichment, and immune infiltration analyses to identify key targets influencing EMT and macrophage polarization. We then constructed PTTG1 knockdown and overexpression cell lines to assess the impact of PTTG1 on cell proliferation, migration, invasion, EMT, and macrophage polarization in vitro. Analysis revealed that differentially expressed genes were enriched in the cGMP-PKG pathway and correlated with M2 macrophages. PTTG1 overexpression in A2780 and SK-OV-3 ovarian cancer cells promoted proliferation, invasion, and migration, while enhancing sGC, PKG1, and PKG2 expression to activate the cGMP-PKG pathway and induce M2 macrophage polarization. PTTG1 knockdown produced opposite results, reinforcing our conclusions. This study uncovers a novel mechanism of PTTG1 in ovarian cancer development and suggests it as a potential therapeutic target.